Reflecting on the care to newborns with very low weight in a neonatal unit: the importance of the concepts - Oliveira, Márcia Maria Coelho; Leitão, Glória da Conceição Mesquita (Rev Rene, 2005)
Bibliographical study developed in a course of the Master’s degree program in Nursing at the Federal University of Ceará, in May, 2004. We aimed at analyzing reflectively the concepts: premature newborn, very low weight, stress and Neonatal Unit. We consulted journals, books on Nursing, Perinatology, Medical Neonatology, official publications by the Ministry of Health, and the course contents. We concluded that the action of defining concepts establishes the clarity of the terms and a better understanding of the pertinent themes. Such considerations are relevant, because they contribute to the development of professionals in the Nursing field and stir the critical awareness of those who carry out the nursing practice.